2019
DOI: 10.1097/ico.0000000000002191
|View full text |Cite
|
Sign up to set email alerts
|

Brillouin Microscopy Visualizes Centralized Corneal Edema in Fuchs Endothelial Dystrophy

Abstract: Purpose-To investigate the feasibility of using Brillouin microscopy for assessment of corneal edema in patients with Fuchs' Endothelial Corneal Dystrophy (FECD). Brillouin microscopy analyzes the frequency shift of light inelastically scattered by naturally occurring acoustic waves in a small volume of tissue. The resulting frequency shift is a measure of the local hydromechanical properties of the tissue.Methods-Participants were scanned using a clinical Brillouin imaging system (780 nm laser, 5 mW) and a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Brillouin frequency shift was shown to have negative correlation with corneal hydration, [ 52 ] which might be helpful in evaluating abnormal hydration change associated with endothelial dysfunction. Eltony et al [ 53 ] revealed that patients with Fuchs' endothelial dystrophy showed a centralized reduction in Brillouin shift, which was consistent with central corneal edema. Brillouin microscopy also detected substantially reduced corneal hydration after Descemet membrane endothelial keratoplasty (DMEK) [ 53 ].…”
Section: Brillouin Microscopymentioning
confidence: 99%
See 2 more Smart Citations
“…Brillouin frequency shift was shown to have negative correlation with corneal hydration, [ 52 ] which might be helpful in evaluating abnormal hydration change associated with endothelial dysfunction. Eltony et al [ 53 ] revealed that patients with Fuchs' endothelial dystrophy showed a centralized reduction in Brillouin shift, which was consistent with central corneal edema. Brillouin microscopy also detected substantially reduced corneal hydration after Descemet membrane endothelial keratoplasty (DMEK) [ 53 ].…”
Section: Brillouin Microscopymentioning
confidence: 99%
“…Eltony et al [ 53 ] revealed that patients with Fuchs' endothelial dystrophy showed a centralized reduction in Brillouin shift, which was consistent with central corneal edema. Brillouin microscopy also detected substantially reduced corneal hydration after Descemet membrane endothelial keratoplasty (DMEK) [ 53 ].…”
Section: Brillouin Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…30 Recently, the effects of water content on frequency shift have been investigated, 31 and Brillouin microscopy has been used to detect the changes in corneal hydration that accompany Fuchs Corneal Dystrophy. 32 From a mechanical standpoint, Brillouin microscopy probes micron-level unit volumes. In this scale, Brillouin microscopy measurements of anisotropy are not sensitive to macro-level changes in hydration unless such changes in hydration affect fiber distribution at a micron-scale level.…”
Section: Introductionmentioning
confidence: 99%